UJI EFEKTIVITAS EKSTRAK DAUN TEMBELEKAN (Lantana camara Linn) DALAM BENTUK GRANUL PADA BUNGA PINK TERHADAP KEMATIAN LARVA Aedes SP - Apriyanto Apriyanto; Kemal Idris Balaka; Riska Amelia Zulkarnain (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Dengue Hemorrhagic Fever (DHF) is a public health problem that appears mostly in the tropics and subtropics in the world. DHF including acute diseases caused by viral infections under the mosquitoes of Aedes aegypti and Aedes Albopictus. In Tembelekan leaves (Lantana camara Linn) contain active compounds namely flavonoids, alkaloids, saponins and tannins which can inhibit the development of mosquitoes and larvae. The purpose of this study was to determine the results of the effectiveness of the extract of the Tembelekan leaf (Lantana camara Linn) in the form of granules as larvicide against the death of larvae of Aedes sp. This research was conducted experimentally with variations in the concentration of 7%, 8%, 9%. 220 Aedes sp larvae were used, divided into 3 concentrations of granules simplicia of the Tembelekan leaves, 7%, 8%, and 9% with 3 repetitions. Abate 1% is used as a positive control. Each concentration contains 20 larvae in 100 mL of water. Observations were made by counting the number of dead larvae. The results of the study showed that the total mortality of larvae using granules simplicia Tembelekan leaves (Lantana camara Linn) at a concentration of 7% by (26%), concentration of 8% as big (53%) at a concentration of 9% by (81%) Keywords: larvae of Aedes sp, Leaves tembelekan, Larvasida